Practical Management of Epileptic Seizures and Status Epilepticus in Adult Palliative Care Patients - Grönheit, Wenke; Popkirov, Stoyan; Wehner, Tim; Schlegel, Uwe; Wellmer, Jörg (Frontiers in Neurology, 2018)
In terminally ill patients, paroxysmal or episodic changes of consciousness, movements and behavior are frequent. Due to ambiguous appearance, the correct diagnosis of epileptic seizures (ES) and non-epileptic events (NEE) is often difficult. Treatment is frequently complicated by the underlying condition, and an approach indicated in healthier patients may not always be appropriate in the palliative care setting. This article provides recommendations for diagnosis of ES and NEE and treatment options for ES in adult palliative care patients, including aspects of alternative administration routes for antiepileptic drugs such as intranasal, subcutaneous or rectal application.